2017
DOI: 10.1017/s0022149x17000116
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial genome ofAncylostoma tubaeformefrom cats in China

Abstract: Ancylostoma tubaeforme may infect canids, felids and humans, and pose a potential risk to public health. Polymerase chain reaction (PCR) techniques were used to amplify the complete mitochondrial (mt) genome sequence of A. tubaeforme from cats and to analyse its sequence characteristics after molecular identification based on the internal transcribed spacer ITS1+ sequence. The results show that the complete mt genome sequence (GenBank accession number KY070315) of A. tubaeforme from cats was 13,730 bp in lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 39 publications
4
20
0
Order By: Relevance
“…As shown in Figure 1, the phylogenic tree placed A. caninum together with species from Ancylostomatinae and separated from species of Bunostominae with high bootstrap confidence, supporting that the Ancylostomatinae and Bunostominae are monophyletic groups in the family Ancylostomatidae. Amongst the subfamily Ancylostomatinae, A. caninum from China and Australia were more closely related to each other than to that from Japan; nevertheless, these three dog-originated A. caninum clustered together and showed a closer genetic relationship to A. tubaeforme (cat hookworm) and A. duodenale (human hookworm) than to A. ceylanicum (dog/cat hookworm) and Uncinaria sanguinis (sea lion hookworm), consistent with recent molecular studies (Shi et al 2017(Shi et al , 2018. In summary, the sequenced A. caninum mtDNA provides insights into phylogenetic studies among Ancylostomatidae nematodes.…”
supporting
confidence: 88%
“…As shown in Figure 1, the phylogenic tree placed A. caninum together with species from Ancylostomatinae and separated from species of Bunostominae with high bootstrap confidence, supporting that the Ancylostomatinae and Bunostominae are monophyletic groups in the family Ancylostomatidae. Amongst the subfamily Ancylostomatinae, A. caninum from China and Australia were more closely related to each other than to that from Japan; nevertheless, these three dog-originated A. caninum clustered together and showed a closer genetic relationship to A. tubaeforme (cat hookworm) and A. duodenale (human hookworm) than to A. ceylanicum (dog/cat hookworm) and Uncinaria sanguinis (sea lion hookworm), consistent with recent molecular studies (Shi et al 2017(Shi et al , 2018. In summary, the sequenced A. caninum mtDNA provides insights into phylogenetic studies among Ancylostomatidae nematodes.…”
supporting
confidence: 88%
“…Adult A. ceylanicum and A. tubaeforme samples were isolated and identified by Liu et al [4] and Shi et al [2], and preserved in 50% ethyl alcohol in our laboratory. Fecal samples were collected from stray cats at the Animal Rescue Station in Shaoguan city of Guangdong province in China and stored at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The main hookworms infecting cats include Ancylostoma ceylanicum , A. tubaeforme , A. braziliense , and Uncinaria stenocephala . The recent investigations have shown that the cat’s hookworm infection in China is mainly caused by A. ceylanicum and A. tubaeforme [1,2]. A. ceylanicum is globally distributed among dogs and cats, however it is particularly severe in Asia, especially in Southeast Asia and the Pacific.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expected fragment is 713 bp. PCR was performed referring to Shi et al [15]. PCR products were examined by 1.5% agarose gel electrophoresis, re-harvested using the OMEGA Gel Extraction Kit (Omega Bio-Tek, Norcross, Georgia, USA) and sent to Sangon Biotech (Shanghai) company for sequencing.…”
mentioning
confidence: 99%